2021
DOI: 10.1016/j.jcv.2021.104760
|View full text |Cite
|
Sign up to set email alerts
|

Development of a point-of-care test to detect SARS-CoV-2 from saliva which combines a simple RNA extraction method with colorimetric reverse transcription loop-mediated isothermal amplification detection

Abstract: The new coronavirus infection (COVID-19) is a major public health concern, with a high burden and risk for infection among patients and healthcare workers. Saliva droplets containing SARS-COV-2 are a major vector for COVID-19 infection, making saliva a promising alternative for COVID-19 testing using nasopharyngeal swab samples. To diagnose COVID-19 patients in the field, a point-of-care test (POCT) using saliva was conceptualized. We have developed a simple method for extracting RNA from saliva samples using … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 15 publications
0
35
0
1
Order By: Relevance
“…One example is the COVID-19 RT-LAMP test developed by Yamazaki et al . which digests saliva with a semi-alkaline protease for 15 min followed by inactivation at 95 °C for 5 min 35 . The SalivaDirect COVID-19 test uses a similar processing method although it utilizes RT-PCR and is therefore not a point-of-care test 33 .…”
Section: Discussionmentioning
confidence: 99%
“…One example is the COVID-19 RT-LAMP test developed by Yamazaki et al . which digests saliva with a semi-alkaline protease for 15 min followed by inactivation at 95 °C for 5 min 35 . The SalivaDirect COVID-19 test uses a similar processing method although it utilizes RT-PCR and is therefore not a point-of-care test 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an investigation into a series of 44 people in Japan suspected of having COVID-19, using a buccal sample yielded a sensitivity of 82.6% over 23 definite COVID-19 patients. Results were obtained in 45 min [ 15 ]. Further investigations using the same commercially available isothermal amplification technology that we evaluated here (ID NOWTM, Abbott, Scarborough, ME, USA) showed 94% positive percent agreement (90/96 nasopharyngeal swabs) in one study [ 20 ] and 91% positive percent agreement (30/33 nasopharyngeal swabs) in another study [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among this emerging technology, loop-mediated amplification (LAMP) and Nicking enzyme-assisted reaction (NEAR) have been used in point of care, far from central laboratories to identify both symptomatic and asymptomatic individuals [ 14 ]. Furthermore, isothermal amplification applied to saliva samples has also proved promising on a limited series of COVID-19 patients [ 15 ]. Moreover, it was recently demonstrated that saliva collection with a roll cotton improved significantly the molecular detection of SARS-CoV-2 compared to nasopharyngeal swab (NPS) specimens [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various methods are available to extract RNA from saliva, such as methods using phenol and guanidinium isothiocyanate, or commercially available silica membrane spin columns or magnetic bead-based RNA isolation kits (63). Other molecular diagnostic methods, such as reverse transcription-loop-mediated isothermal amplification (RT-LAMP), have also been reported as useful for diagnosing COVID-19 in settings of point-of care testing (64)(65)(66). Rapid and extraction-free detection of SARS-CoV-2 from saliva by colorimetric RT-LAMP is a simple, sensitive, rapid, and cost-effective approach with broad potential to expand diagnostic testing for the virus causing COVID-19 (67,68).…”
Section: Obstacles To Sars-cov-2 Rna Extraction From Saliva and New Applicationsmentioning
confidence: 99%